Upstream promoter elements of the herpes simplex virus type 1 glycoprotein H gene. - Steffy, K R (1991)
To investigate the cis-acting sequence elements that are involved in the regulation of herpes simplex virus type 1 late-gene expression, recombinant viruses were constructed that express the Escherichia coli lacZ gene from the promoter of the glycoprotein H (gH) gene. Deletion experiments established an upstream boundary for the gH promoter of no more than 83 bp from the start of gH transcription and showed that the promoter sequences did not overlap with coding sequences of the upstream thymidine kinase (tk) gene. Sequences of the tk gene previously shown to be required for efficient processing of the tk transcript were essential for expression form the gH promoter and included a TATA-like element. In addition, the gH TATA element was specifically mutagenized to substitute the TATA elements of immediate-early, early, and other late viral promoters for the gH TATA element. The results indicated that the TATA element was an interchangeable component of herpes simplex virus type 1 promoters and did not regulate temporal expression.